الشّيخ العروسي حويتي ودوره في الإصلاح (1948 - 1954م) بقرية الجُدَيْدة الشرقية – الدّبيلة - بوعافيه, فتحي; فائزي, أحمد (University of Eloued جامعة الوادي, 2022)
ما من شكّ أنّ الجهود الثّقافيّة لرجالات الإصلاح في مختلف ربوع الوطن أثناء الحقبة الاستعمارية شكّلت أكبر مقاومة للسياسة الفرنسية، القائمة أساسا على مبدأ التّجهيل وطمس هويّة المجتمع حتّى تتمكّن من التّغلغل والسّيطرة على مختلف مقوّماته، فكانت جهود أعلام الفكر الإصلاحي في الجنوب الشّرقي الجزائريّ ما بين "1900-1962م" بمثابة الحصن الواقي والسدّ المنيع في وجه تلك المحاولات... ولعلّ الشّيخ "العروسي حويتي" ومن خلال تتبّعنا لمسيرته الإصلاحيّة والدّعويّة، يعتبر من أبرز أعلام المقاومة الثقافية بوادي سوف عموما، و بقرية "الجديدة" على وجه الخصوص، حيث كان له الأثر الكبير في تحوّل هذه البلدة إلى واحدة من أكثر المناطق ثوريّة، بل والأُولى من حيث عِداد المجاهدين والشّهداء الّذين تفخر بهم ولاية الوادي، وما تلميذه الشّهيد القائد "حمّه لخضر" ورفاقه الّذين خاضوا أكبر المعارك ضدّ المستعمر، إلّا خير دليل على نتائج تلكم الجهود الّتي قام بها الشّيخ. سنسعى في هذه الورقة البحثيّة إلى إبراز الجهود الإصلاحيّة، لاسيما الدّعويّة منها والعلميّة الّتي كرّسها الشّيخ "العروسي حويتي السّوفي" ما بين (1948-1954م)، بقرية الجديدة (بلديّة الدّبيلة حاليّا)، والتي تجلّى أثرها في شباب وأهالي البلدة إبّان تلك الفترة، وذلك من خلال تتبّع مختلف تحرّكاته وأعماله وآثاره، واستنادا إلى ما يرويه تلامذته عن أهمّ أنشطته ومواقفه من المستعمر الفرنسيّ، هذا الأخير الّذي رأى في آرائه وأفكاره خطرا على خططه الاستعمارية، فقام بإيذائه واعتقاله في محاولة منه لتجفيف منابع المقاومة وطمس معالمها. Abstract : The cultural efforts of men of reform throughout the homeland during the colonial era have undoubtedly been the greatest resistance to French politics, based mainly on the principle of ignorance and obliteration of the identity of society so that it can permeate and control its various components. The efforts of reformist in the south-eastern Algerian between 1900-1962 served as a fortress. Perhaps Sheikh "Arossi Huiti" and through our tracking of his reform and ,advocacy ,propaganda career, he is one of the most prominent figures of cultural resistance in Oued Souf in general, and in the village Al-Jadida in particular, it had a significant impact on the transformation of this town into one of the most revolutionary areas, even in terms of the number of Mujahideen and martyrs who Willaya Eloued, proud of them , and his pupil the martyr, the leader Hamma Lakhdar " and his comrades who fought the biggest battles against the colony the best evidence of his efforts. In this paper, we will endeavor to highlight the reform efforts, especially ,the advocacy, the propaganda , especially the scientific devoted by Sheikh " Arossi Huiti Soufi" between (1948-1954), in the village Al-Jadida (current municipality of Al-Debila), its effect which was reflected on the youth and people of the town during that period by tracking his various movements, actions and effects, and based on his students' accounts of his most important activities and attitudes towards the French colony who saw his opinions and ideas as dangerous to his colonial plans, He abused and arrested him in an attempt to drain the sources of resistance and obliterate its features.
مداخلة
Keywords: العروسي حويتي؛ حمّه لخضر؛ الجُديْدة؛ سوف; Arossi Huiti; Hamma Lakhdar; Al-Djedaida; Souf.